Problematika Dakwah di Jorong Kampung Baru Kecamatan Kinali Kabupaten Pasaman Barat - Sastika Dewi; Fajri Ahmad (Bahasa Indonesia, 2024)
The problems of da'wah are problems that arise in inviting, summoning, inviting and entertaining with the process handled by da'wah activities carried out by da'wah. Problems emerged in Jorong Kampung Baru caused by internal and external problems for both dai and mad'u. Internal problems are problems that originate from within the dai or mad'u themselves, while external problems are problems that originate from outside the dai and mad'u as part of da'wah activities. This research aims to find out, describe and analyze the problems of da'wah that occur in Jorong Kampung Baru, Kinali District, West Pasaman Regency. The researcher used Amin S.M's theory with a type of field research with a descriptive research method with a qualitative approach. This research uses data collection techniques, namely observation, interviews and documentation. The results of the research show that there are internal problems that occur in dai and mad'u. The internal problems of the preacher occurred when delivering da'wah in Jorong Kampung Baru, namely the lack of understanding of the preacher and the weak competence of the preacher, while the internal problem of Mad'u was Mad'u's lack of enthusiasm in participating in da'wah activities. Apart from that, it also shows that there are external problems with dai and mad'u, including economic aspects, educational aspects, technological aspects of dai, and economic aspects of mad'u. Of course, this is a problem in the da'wah process in Jorong Kampung Baru, Kinali District, West Pasaman Regency.